Birth weight and adult cancer incidence: large prospective study and meta-analysis. - Yang, T; Reeves, G; Green, J; Beral, V; Cairns, B (Oxford University Press, 2014)
BACKGROUND: Most evidence about associations between birth weight and adult cancer risk comes from studies linking birth records to cancer registration data, where information on known risk factors for cancer is generally lacking. Here, we report on associations between birth weight and cause-specific cancer risk in a large cohort of UK women, and investigate how observed associations are affected by other factors. METHODS: A total of 453 023 women, born in the 1930s and 1940s, reported their birth weight, maternal smoking, parental heights, age at menarche, adult height, adult smoking, and many other personal characteristics. They were followed for incident cancer. Using Cox regression, relative risks by birth weight were estimated for cancers with more than 1500 incident cases, adjusting for 17 potential confounding factors, individually and simultaneously. RESULTS: Birth weight reported in adulthood was strongly correlated with that recorded at birth (correlation coefficient = 0.78, P < 0.0001). Reported birth weight was associated with most of the potential confounding factors examined, the strongest association being with adult height. After 9.2 years follow-up per woman, 39 060 incident cancers were registered (4414 colorectal, 3175 lung, 1795 malignant melanoma, 14 542 breast, 2623 endometrial, 2009 ovarian, 1565 non-Hodgkin lymphoma, and 8937 other cancers). Associations with birth weight were null or weak and reduced after adjustment by adult height (P[trend] > 0.01 for every cancer, after adjustment). In contrast, adult height was strongly related to the risk of every cancer except lung cancer, after adjusting for birth weight and other factors (P[trend] < 0.0001 for most cancers). For lung cancer, adjusting for smoking reduced the association with birth weight. Meta-analyses were dominated by our findings. CONCLUSION: Birth weight and adult height are correlated and likely to be markers of some aspect of growth that affects cancer risk in adulthood. However, birth weight adds little, if any, additional information to adult height as a predictor of cancer incidence in women.